2011
DOI: 10.1111/j.1469-7610.2011.02457.x
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ self‐reported suicide attempts, self‐harm thoughts and their correlates across 17 European countries

Abstract: Although self-reported self-harm thoughts and suicide attempts vary in prevalence within Europe, there are common correlates across countries. These have an important impact on understanding the phenomenon of suicide among young people and in guiding prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
161
7
20

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(208 citation statements)
references
References 39 publications
20
161
7
20
Order By: Relevance
“…One study performed in seven EU countries reported that 24% of adolescents who had made a suicide attempt, made a second attempt within a year [6]. In a similar study, performed in 17 EU countries, it was noted that the median prevalence of any lifetime self-reported suicide attempt was 10.5% across the participant countries (range 4.1%-23.5%) [7].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…One study performed in seven EU countries reported that 24% of adolescents who had made a suicide attempt, made a second attempt within a year [6]. In a similar study, performed in 17 EU countries, it was noted that the median prevalence of any lifetime self-reported suicide attempt was 10.5% across the participant countries (range 4.1%-23.5%) [7].…”
Section: Introductionmentioning
confidence: 89%
“…The predictive role of psychiatric disorder and past history are well recognized in adolescent suicide attempt, but the role of social and cultural factors is less clear [7]. Advancing our understanding of the influence of underlying cultural and sociological factors in adolescent's suicide attempts will allow clinicians to make a more efficient prediction, prevention and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, the subjective SEP and smoking was measured by a single item. However, the recent previous studies focusing on the various racial and ethnic groups have used this self-reported single question method, and this trend has increased in the recent years (Kokkevi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, smoking status was defined on the self-reported data. Nonetheless, self-reports have been suggested to provide more valid information than other methods on the sensitive issues, especially among the adolescent age groups (Kokkevi et al, 2012). Thirdly, the subjective SEP and smoking was measured by a single item.…”
Section: Discussionmentioning
confidence: 99%
“…Limited or lack of social support is recognized as a pervasive predisposing risk factor for suicide. Low socioeconomic status has been linked to suicidal behavior (117). Low levels of parental education are associated with higher adolescent suicidal risk.…”
Section: Social Risk Factorsmentioning
confidence: 99%